Diversifying power : why we need antiracist, feminist leadership on climate and energy - Stephens, Jennie (Island Press, 2020)
The climate crisis is a crisis of leadership. For too long too many leaders have prioritized corporate profits over the public good, exacerbating climate vulnerabilities while reinforcing economic and racial injustice. Transformation to a just, sustainable renewable-based society requires leaders who connect social justice to climate and energy. During the Trump era, connections among white supremacy, environmental destruction, and fossil fuel dependence have become more conspicuous. Many of the same leadership deficiencies that shaped the inadequate response in the United States to the coronavirus pandemic have also thwarted the US response to the climate crisis. The inadequate and ineffective framing of climate change as a narrow, isolated, discrete problem to be "solved" by technical solutions is failing. The dominance of technocratic, white, male perspectives on climate and energy has inhibited investments in social change and social innovations. With new leadership and diverse voices, we can strengthen climate resilience, reduce racial and economic inequities, and promote social justice. In Diversifying Power, energy expert Jennie Stephens argues that the key to effectively addressing the climate crisis is diversifying leadership so that antiracist, feminist priorities are central. All politics is now climate politics, so all policies, from housing to health, now have to integrate climate resilience and renewable energy. Stephens takes a closer look at climate and energy leadership related to job creation and economic justice, health and nutrition, housing and transportation. She looks at why we need to resist by investing in bold diverse leadership to curb the "the polluter elite." We need to reclaim and restructure climate and energy systems so policies are explicitly linked to social, economic, and racial justice. Inspirational stories of diverse leaders who integrate antiracist, feminist values to build momentum for structural transformative change are woven throughout the book, along with Stephens' experience as a woman working on climate and energy. The shift from a divided, unequal, extractive, and oppressive society to a just, sustainable, regenerative, and healthy future has already begun. But structural change needs more bold and ambitious leaders at all levels, like Alexandria Ocasio-Cortez with the Green New Deal, or the Secwepemc women of the Tiny House Warriors resisting the Trans Mountain pipeline. Diversifying Power offers hope and optimism. Stephens shows how the biggest challenges facing society are linked and anyone can get involved to leverage the power of collective action. By highlighting the creative individuals and organizations making change happen, she provides inspiration and encourages transformative action on climate and energy justice.